AKU TELAH SEMBUH: Pengalaman Doktrinal Sebagai Kenyataan Sosio-Teologis Pantekosta - Elia Tambunan; Sang Putra Immanuel Duha (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
This article is written in a social research landscape with Pentecostal theology, namely divine healing as an object of study, by using a critical study method of literary sources, including social media. The question to be answered for the academic field in Indonesia is how to modernize theology as a science that integrates with social science. So far there is a scientific problem. The Bible as the main object of study is too focused on the analysis of biblical texts. Science in these institutions seems to be ignorant of social praxis. The Bible contains narratives of the experience, and history of tribes, societies, and nations. We build our meaning of social theories with systematic theology to produce a theoretical framework. The findings, "I have been healed", not only as a theological expression but has a broad social impact. Through it, we contribute a framework of Pentecostal socio-theological reality to the study of global Pantecostalism which is useful as an empirical working tool in understanding the experiences of biblical text societies and contextual societies.ABSTRAKIni adalah tulisan dalam lansekap penelitian sosial dengan teologi Pantekosta yakni kesembuhan Ilahi sebagai objek kajian, dilakukan dengan metode studi kritik sumber literatur, termasuk media sosial. Pertanyaan yang hendak dijawab untuk ladang akademik di Indonesia, bagaimana cara untuk memodernisasi teologi sebagai ilmu mengintegrasikan dengan sosial sains? Sejauh ini memang ada problem keilmuan. Alkitab sebagai objek utama dari studi terlalu berkutat pada analisis teks biblis. Keilmuan dalam institusi tersebut terkesan abai dengan praksis sosial. Padahal, Alkitab memuat narasi pengalaman, sejarah puak-puak, masyarakat, bangsa-bangsa. Kami membangun pemaknaan sendiri atas teori-teori sosial dengan teologi sistematika untuk menghasilkan kerangka teori. Dalam temuan kami, “aku telah sembuh”, tak hanya sebagai ungkapan teologis tetapi memiliki impak sosial luas. Lewat temuan, kami menyumbangkan kerangka pikir kenyataan sosio-teologis Pantekosta untuk studi Pantekostalisme global yang berguna sebagai alat kerja empiris dalam memahami pengalaman masyarakat teks biblis dan masyarakat kontekstual.Kata Kunci: Kenyataan Sosio-Teologis; Pantekosta; Pengalaman Doktrinal; Teologi Sistematika